Modelling the Extraction of Pectin towards the Valorisation of Watermelon Rind Waste - Méndez, Daniel Alexander (Foods, 2021)
Watermelon is the second largest fruit crop worldwide, with great potential to valorise its rind waste. An experimental design was used to model how extraction parameters (temperature, pH, and time) impact on the efficiency of the process, purity, esterification degree, monosaccharide composition and molar mass of watermelon rind pectin (WRP), with an insight on changes in their structural properties (linearity, branching degree and extraction severity). The models for all responses were accurately fitted (R(2) > 90%, lack of fit p ≥ 0.05) and experimentally validated. At optimum yield conditions, WRP yield (13.4%), purity (540 µg/g galacturonic acid) and molar mass (106.1 kDa) were comparable to traditional pectin sources but showed a higher branching degree with longer galactan side chains and a higher protein interaction. Harsher conditions (pH 1) generated purer homogalacturonan fractions with average molar masses (80 kDa) at the expense of yield, while mild extraction conditions (pH ≥ 2) produced highly branched entangled pectin structures. This study underlines novel compositional features in WRP and the possibility of producing novel customized pectin ingredients with a wider potential application scope depending on the targeted structure.